Public-private partnership as a strategy for universalization of basic sanitation in brazil: case study of sanitary sewage in Ceará - Xavier, Isabel de Oliveira; Silva Neto, Dimas de Castro e (Brazilian Journal of Production Engineering, 2024)
Basic sanitation is a Brazilian constitutional right that involves the provision of water supply, sewage, urban drainage and solid waste management services, in an effective and universal manner. However, small and medium-sized Brazilian municipalities face difficulties in implementing these services due to the high investments required. To encourage investments in this sector, the National Bank for Economic and Social Development (BNDES) led a process of supporting concessions in Brazilian infrastructure through the Investment Partnership Program (PPI), which structured the public-private partnership project between the Ceará Water and Sewage Company (Cagece) and private companies. In addition to this, Law N° 14.026 (2020) was approved, which established the goal of universalizing Brazilian basic sanitation by the year 2033. Therefore, this work analyzed, through an explanatory case study, the contractual aspects of structuring of the administrative concession agreement for sewage services in Ceará, with the aim of explaining the reasons that resulted in the choice of this modality. After the case study, it was concluded that adequate risk allocation contributed to the choice of the administrative concession for the universalization of sewage services by the state of Ceará.
Keywords: Public Private; Partnership; Infrastructure; Sewage; Structuring; Cagece; Concession; Investment; Risks